Early visual deprivation results in a degraded motor map in the optic tectum of barn owls. - du Lac, S (1991)
The optic tectum contains a precise map of orienting movements: the size and direction of movements of the eyes, head, and/or body vary systematically with the locus of neural activation within the tectum. In adult animals, this motor map aligns closely with the tectal map of visual space. This study addressed the question of whether the motor map develops entirely independently of visual experience. We found that in barn owls (Tyto alba) raised without vision, although a tectal map of head movement develops, its topography and alignment with the map of visual (and auditory) space are abnormal. The results demonstrate that during early life vision is necessary either to maintain or to guide the development of a normal tectal motor map.